Perekrutan Tentara Anak Dalam Konflik Bersenjata Ditinjau Dari the Optional Protocol to The Convention on The Rights of The Child on The Involvement of Children in Armed Conflict 2000 - Risamena, Agnesya Syedeline; Tahamata, Lucia Charlota Octovina; Hattu, Vondaal Vidya (Faculty of Law Universitas Pattimura, 2025)
The Optional Protocol to the Convention on the Rights of the Child on the Involvement of Children in Armed Conflict of 2000 is an international legal instrument designed to protect children from recruitment and direct involvement in armed conflict. However, in reality, violations of the provisions of this protocol still frequently occur in various conflict zones. The practice of recruiting children by armed groups not only contradicts the content of the protocol but also violates the fundamental principles of International Humanitarian Law and Human Rights. This study uses a normative legal method with a regulatory approach, international document studies, a conceptual approach, and a case approach to examine the effectiveness of the protocol's implementation. Data was obtained through literature studies and analyzed qualitatively based on primary, secondary, and tertiary legal materials. The results of the study show that this protocol regulates preventive protection measures, such as prohibiting the recruitment of children under the age of 18, as well as repressive protection through criminalization, sanctions, victim recovery, and inter-state cooperation, to the extent that the protocol requires a mechanism for regular monitoring and reporting to the Committee on the Rights of the Child. The case in Mozambique reflects non-compliance with reporting obligations since 2006, underscoring the importance of strengthening monitoring systems as a means of evaluating and improving child protection policies, as well as optimizing the implementation of this protocol at the national and international levels.